Democracy and moral pluralism - Polo Santillán, Miguel Angel (2020)
In July of last year, the prosecutor's office asked the dean of the Faculty of Letters of the UNMSM for a report on some conferences whose theme had been Marxism. Undoubtedly, this was out of place, if we consider that we live in a democracy. Perhaps these are still fears from the 80s and 90s of the last century, given that the terrorist group Shining Path was fueled by Marxism, as interpreted by its leader.